Effect of Nanoparticles Surface Charge on the Arabidopsis thaliana (L.) Roots Development and Their Movement into the Root Cells and Protoplasts - Milewska-Hendel, Anna; Zubko, Maciej; Stróż, Danuta; Kurczyńska, Ewa U (International journal of molecular sciences, 2019)
Increasing usage of gold nanoparticles (AuNPs) in different industrial areas inevitably leads to their release into the environment. Thus, living organisms, including plants, may be exposed to a direct contact with nanoparticles (NPs). Despite the growing amount of research on this topic, our knowledge about NPs uptake by plants and their influence on different developmental processes is still insufficient. The first physical barrier for NPs penetration to the plant body is a cell wall which protects cytoplasm from external factors and environmental stresses. The absence of a cell wall may facilitate the internalization of various particles including NPs. Our studies have shown that AuNPs, independently of their surface charge, did not cross the cell wall of Arabidopsis thaliana (L.) roots. However, the research carried out with using light and transmission electron microscope revealed that AuNPs with different surface charge caused diverse changes in the root's histology and ultrastructure. Therefore, we verified whether this is only the wall which protects cells against particles penetration and for this purpose we used protoplasts culture. It has been shown that plasma membrane (PM) is not a barrier for positively charged (+) AuNPs and negatively charged (-) AuNPs, which passage to the cell.
Keywords: Surface Properties; Arabidopsis; kovové nanočástice; Protoplasts; Cell Wall; kořeny rostlin; Plant Roots; povrchové vlastnosti; protoplasty; Metal Nanoparticles; buněčná stěna